Understanding Formative and Summative Assessment for EFL Teachers: Theoretical Reflections on Assessment for Learning. - Ridhwan, M. (Program Studi Pendidikan Bahasa Inggris FKIP UIR, 2017)
The literatures showed that the important of assessment has brought so significance works and studies. Currently, the teacher’s conception and belief to conduct assessment being questioned because of its nature, the cheating habit among students while assessing summative kind of test becomes the roots of all the problems occurred during the classroom test. They, especially EFL teachers should not determine by the test as the only gear to measure learning outcomes, using formative as assessment for learning is better proposed and understood rather than spotlighting the assessment of learning. Dispute summative can someway use feedback for formative purpose, it seems the roles of the teachers would take so little function for students’ improvement. It is then suggested for EFL teachers, they should immense formative procedures over summative to enhance the learning target which has been previously shared with students. Eventually, if it is successfully offered and applied massively by teachers, the earlier problems found such as cheating, lower students’ grade, would be diminished, and positively change the learning behavior. In addition, will not possible to transform teachers’ conception and practice from being an “assessment of learning” into assessment for learning”. The formative teachers will always examine their students based on the dynamic situation of their students, they viewed every dynamic problem found during classroom teaching and learning could be as feedback for teaching improvement and re-designed their teaching method in the classroom.